Material Deprivation, Social Class and Life Course in the Balkans, Eastern Europe and Central Asia - Gugushvili, Alexi (Studies of Transition States and Societies, 2011)
This paper employs the factor analysis technique and data from the UNDP/UNICEF Social Inclusion Survey to construct a material deprivation index for ﬁ ve transitional societies in the Balkans (FYR Macedonia and Serbia), Eastern Europe (Moldova and Ukraine) and Central Asia (Kazakhstan). The distribution of deprivation between these societies can be largely explained by their level of economic development, but within-county variance is not limited to monetary dimension. Controlling for settlement type, human capital and employment status in multivariate settings, the paper tests the hypothesis of the continuous importance of occupational social class and the emerging role of diﬀ erent life phases in individuals’ welfare outcomes. The results reveal that all speciﬁ ed social classes and most of the deﬁ ned life phases have diverse and statistically signiﬁ cant eﬀ ects on the constructed deprivation index and the likelihood of being under 70 per cent of the median deprivation threshold. Belonging to non-skilled manual, farmers and skilled manual social class as well as being a child or lone parent were revealed to have the highest risk of material deprivation. These ﬁ ndings are in line with the conclusions made for the Western welfare democracies on the complementary nature of social class and life course dimensions in explaining social hardship.